EL ENFOQUE CONSTRUCTIVISTA EN EL CURRICULUM DE ENFERMERÍA: motivación, dificultades y demandas que enfrenta el o la docente. - Rojas Valenciano, Ligia (2005)
This article is a qualitative  research product in which it applied like a research structural method the “Action Research”. The techniques used for the recollecting information was the no participate observation, the semi structural interview and the field diary. The sample was intentional and it participated 12 professor; they work in the mental and psiquiatric area, medicine-surgery area and sexual and reproductive area. The validity was made knowing my position and  reflexion of my person; besides, the triangulation of the techniques used and the intersubjective. The motivation for researching this theme was born like a professor suspicious to explore new fields in the educational area, specifically in nursing.